1998
DOI: 10.1080/003655998750015656
|View full text |Cite
|
Sign up to set email alerts
|

Juxtaglomerular Cell Tumor without Hypertension

Abstract: Juxtaglomerular cell tumors are rare. This report presents a case of juxtaglomerular cell tumor without hypertension. All previously reported cases showed marked hypertension, whereas this is the first case of juxtaglomerular cell tumor without hypertension. The immunohistochemistry and ultrastructure of this case are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 4 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…This may be related to the JCT originating from the modified smooth muscle cells that comprises the vascular component of the juxtaglomerular apparatus. [ 20 21 ] Juxtaglomerular cells are near the pelvis parenchyma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be related to the JCT originating from the modified smooth muscle cells that comprises the vascular component of the juxtaglomerular apparatus. [ 20 21 ] Juxtaglomerular cells are near the pelvis parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…The renal angiographic findings also showed a hypovascular area or no abnormal vascularities. [ 3 21 25 ] The pathology of the JCTs, however, contained a prominent vasculature. [ 20 ] Our study and another report[ 2 ] showed a mild enhancement in most cases of JCT.…”
Section: Discussionmentioning
confidence: 99%
“…Second most common presentation is the atypical variant showing hypertension with normal potassium level [8]. The third, non-functioning variant is very rare and is characterized by a normal blood pressure and normal potassium level [14-16]. Clinicians should strongly suspect JGCT if they encounter adolescent or young adult patients with severe or even moderate hypertension associated with an unexplained secondary hyperaldosteronism [6].…”
Section: Introductionmentioning
confidence: 99%